2008
DOI: 10.1037/1072-5245.15.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a cognitive-behavioral intervention for adolescents.

Abstract: The aim of this study was to evaluate the effect of a cognitive-behavioral, biofeedback-assisted intervention to impart skills for coping with stressful encounters in a nonclinical adolescent population. Israeli Arab and Israeli Jewish participants completed pre-and postintervention questionnaires assessing state anxiety, test anxiety, behavior symptoms, hostility, and selfesteem. Electrodermal activity was recorded using biofeedback. From pre-to postintervention, scores of state anxiety, test anxiety, behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
3
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 38 publications
1
36
3
10
Order By: Relevance
“…An isolated skin conductance coupler applied a constant 0.5 V potential across the electrode pair. The finger sensors measured the galvanic skin response (GSR) e electrical changes in the skin that are affected by sweat gland activity in response to physical, emotional and mental states (Leahy et al, 1998;Nagai et al, 2004;Shapiro et al, 2007;Yahav & Cohen, 2008).…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…An isolated skin conductance coupler applied a constant 0.5 V potential across the electrode pair. The finger sensors measured the galvanic skin response (GSR) e electrical changes in the skin that are affected by sweat gland activity in response to physical, emotional and mental states (Leahy et al, 1998;Nagai et al, 2004;Shapiro et al, 2007;Yahav & Cohen, 2008).…”
Section: Apparatusmentioning
confidence: 99%
“…Autonomic arousal levels were measured by the same biofeedback apparatus (Prorelax interactive program, version 4.0, Mindlife, Jerusalem, Israel) used in our previous work examining relaxation abilities (Lazarov et al, 2010), earlier versions of which were shown in previous studies to provide reliable measures of autonomic arousal levels in various clinical contexts (Leahy, Clayman, Mason, Lloyd, & Epstein, 1998;Nagai, Goldstein, Fenwick, & Trimble, 2004;Shapiro, Melmed, Sgan-Cohen, Eli, & Parush, 2007;Yahav & Cohen, 2008). As in Lazarov et al (2010), monitoring was done by two Velcro strapped electrodes applied to the fingertips of the second and forth digits of the right hand.…”
Section: Apparatusmentioning
confidence: 99%
“…Furthermore, random assignment at the classroom level introduced the potential for contamination of control groups housed in the same school as the intervention groups (Yahav & Cohen, 2008). Three of the four studies that randomized at the group level reported a data analysis plan that accounted for clustering (Barnes et al, 2004;Jellesma & Cornelis, 2012;Yahav & Cohen, 2008).…”
Section: Study Designsmentioning
confidence: 98%
“…Nine of the studies (60%) used randomized designs with the unit of randomization being at the individual level for five of the studies (Barnes, Treiber, & Davis, 2001;Davey & Neff, 2001;Hains & Szyjakowski, 1990;Weigensberg et al, 2009;Wright, Gregoski, Tingen, Barnes, & Treiber, 2011) and the group level (e.g., school, classroom) for four studies (Barnes, Treiber, & Johnson, 2004;Jellesma & Cornelis, 2012;White, 2012;Yahav & Cohen, 2008). Those that randomized at the group level had two of five schools or classrooms in the study to randomly assign to intervention or control conditions, which was not adequate to ensure confounders would be equally distributed across the sample (Barnes et al, 2004;Jellesma & Cornelis, 2012;White, 2012;Yahav & Cohen, 2008).…”
Section: Study Designsmentioning
confidence: 99%
See 1 more Smart Citation